On the C.E. degrees realizable in II⁰₁ classes - Csima, Barbara F. (2023)
We study for each computably bounded Π01 class P the set of degrees of c.e. paths in P. We show, amongst other results, that for every c.e. degree a there is a perfect Π01 class where all c.e. members have degree a. We also show that every Σ03 set of c.e. indices is realized in some perfect Π01 class, and classify the sets of c.e. degrees which can be realized in some Π01 class as exactly those with a computable representation.